Effects of using the Nintendo Wii Fit Plus Platform in the sensorimotor training of gait disorders in Parkinson's disease - Giovanna Barros Gonçalves; Marco Antônio A. Leite; Marco Orsini; João Santos Pereira (MDPI AG, 2014)
The use of the Nintendo Wii has been considered a good alternative in the motor rehabilitation of individuals with Parkinson's disease (PD), requiring simultaneous interaction to develop strategies for physical, visual, auditory, cognitive, psychological and social activities in the performing of virtual activities, resulting in improvement in functional performance and gait. The aim of this study was to analyze the effect of virtual sensorimotor activity on gait disorders in people with PD. Fifteen subjects with a clinical diagnosis of PD were submitted to the Unified Parkinson's Disease Rating Scale (UPDRS III), Schwab and England Activities of Daily Living Scale (SE), Functional Independence Measure (FIM), and biomechanical gait analysis using digital images taken with a video camera before and after the treatment program. The activities with the Nintendo Wii virtual platform were standardized into three categories: aerobics, balance and Wii plus exercises. Participants carried out separate virtual exercises for 40 min, twice a week, for a total of 14 sessions. The program improved sensorimotor performance in PD gait, with an increase in stride length and gait speed, in addition to a reduction in motor impairment, especially in items of rigidity and flexibility of the lower limbs evaluated by UPDRS III, and greater functional independence, as evidenced in the SE and FIM scales. Improvements in items related to locomotion and stair climbing were also observed. The training was effective in motor recovery in chronic neurodegenerative diseases, showing improvement in motor performance and functional independence in individuals with PD.